Apropriate Agronomic Practices for Pest and Disease Management - R. B., Negalur; Guruprasad, G. S.; S. B., Gowdar; G., Narappa (International Journal of Bio-resource and Stress Management, 2017)
Pesticides play important role in agricultural production by means of increasing crop yield and farmer’s income. The indiscriminate use of chemicals has resulted in a reduction of biodiversity of natural enemies, outbreak of secondary pests, development of resistance to pesticides and contamination of food and ecosystem, Agronomic measures of pest management involves variations in usual farm operations which are being usually preventive and indirect, they are the cheapest of all the control measures The principle involved in the agronomic management of insect pest and disease is purposeful manipulation of the environment to make it less favorable for their incidence by exerting economic control on the pest or at least reducing their rate of increase/damage. Due to sustained increasing problems from massive applications of pesticides, like insect resistance to pesticides, resurgence of pests, pollution of food and feed, health hazards, toxicity towards plants and animals and environmental pollution. One way to minimize these effects is use of biotechnological tools for alleviating biotic stresses, which explore how the tools of biotechnology can be used in pest management for sustainable crop production and environmental conservation. Another way is through cultural control including all those techniques that will make the environment less favorable for pests to develop or multiply, but which still favors crop production. Insect pest and disease management in its broadest sense includes everything that makes the life difficult for insects that kill them or prevents their increase and make it laborious for them to spread about the world.